Environmental education for the reduction of the use of agrochemicals in the Balsa en Medio community (Ecuador) - Aveiga Ortiz, Ana María (2021)
Environmental education is an effective tool to apply sustainable production techniques. The objective of this research was to apply environmental education strategies to reduce the use of agrochemicals in the Balsa en Medio community (Ecuador). Using Likert-type scales, a diagnosis was made of the level of knowledge and environmental behavior of the community members. Afterwards, the training plan was implemented applying environmental strategies on the preparation and application of compost, bioles, bioinsecticides and biopreparations with efficient microorganisms in seasonal crops. Finally, the final environmental knowledge and behavior of the participants was evaluated. The results of the diagnosis revealed that 100% of the participants presented a deficient environmental knowledge, while 98% of participants showed inappropriate environmental behavior. After applying an environmental education program, it was obtained that 21.15% of participants showed excellent environmental knowledge; 61.54% were in the good category and the remaining 17.31% revealed little knowledge; For environmental behavior, 44.23% of participants were adequate, in contrast, 55.77% showed inadequate environmental behavior. The workshops given in the community made it possible to significantly increase the level of environmental knowledge and behavior.